2011
DOI: 10.1378/chest.10-2869
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Quality of Life in Patients With COPD

Abstract: Multiple studies have demonstrated signifi cant impairment in the health-related quality of life (HRQL) in subjects with COPD. 1 The concept of HRQL relates to disparity between an individual's desired and real-life well being as infl uenced by his or her health. 2 Many factors have been reported to infl uence HRQL in COPD, including lung function, exercise capacity, depression, and level of education. 3,4 Little has been published, however, regarding the infl uence of race on HRQL. Until recently, many clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
5
41
0
Order By: Relevance
“…Similar to comparisons presented between the AA and NHW participants with GOLD Stage I-IV (22), AA participants were younger, more likely to be current smokers, smoked less than NHWs, but had similar levels of lung function impairment. AAs were also more likely to carry a diagnosis of asthma and to have held a dusty job (Table 1).…”
Section: Resultssupporting
confidence: 60%
“…Similar to comparisons presented between the AA and NHW participants with GOLD Stage I-IV (22), AA participants were younger, more likely to be current smokers, smoked less than NHWs, but had similar levels of lung function impairment. AAs were also more likely to carry a diagnosis of asthma and to have held a dusty job (Table 1).…”
Section: Resultssupporting
confidence: 60%
“…Th ese fi ndings illustrate the complexity of the ethnic diff erences in disease impact in OLD, which are present not just between non-Hispanic whites and Mexican Americans but also between non-Hispanic whites and African Americans because it has been proven by other researchers. For example, in analyses comparing non-Hispanic whites and African Americans with COPD in the COPDGene (Genetic Epidemiology of COPD) cohort, Han et al 5 found similar HR-QOL in the absence of exacerbations but worse HR-QOL for African Americans who had experienced exacerbations. In the present analyses, we tried to advance the current knowledge to identify possible casual pathways of poorer HS in Mexican Americans with OLD.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of racial diff erences in HR-QOL in patients who have experienced exacerbations of COPD showed worse HR-QOL in African Americans . 5 However, minimal research has been done on diff erences in HR-QOL in other racial or ethnic groups with OLD.…”
mentioning
confidence: 99%
“…African Americans and Puerto Ricans share both a significant proportion of African ancestry and a high burden from lung diseases such as asthma and chronic obstructive pulmonary disease (12). Whereas African ancestry has been associated with reduced FEV 1 and FVC in African American adults without asthma (13) and Puerto Rican children (with and without asthma) (14), Native American ancestry has been associated with higher FEV 1 and reduced risk of chronic obstructive pulmonary disease in adults from New Mexico (15).…”
mentioning
confidence: 99%
“…Work in animal models of inflammation-induced airway remodeling demonstrates an increase in the fraction of ASM within the airway showing markers of cell cycle progression (i.e., proliferation). However, several studies have reported that ASM cells of individuals with severe asthma do not show increased frequency of expression of cell cycle progression markers, such as cyclin D1 and proliferating cell nuclear antigen (PCNA) in post mortem specimens (12), or in biopsies, measuring either cyclin D1 (2) or Ki67 (13). A more recent biopsy study reports increases in Ki67 and proliferating cell nuclear antigen frequency in severe asthma (14).…”
mentioning
confidence: 99%